Mental toughness, sleep disturbances, and physical activity in patients with multiple sclerosis compared to healthy adolescents and young adults - Sadeghi Bahmani D; Gerber M; Kalak N; Lemola S; Clough PJ; Calabrese P; Shaygannejad V; Pühse U; Holsboer-Trachsler E; Brand S (Neuropsychiatric Disease and Treatment)
Dena Sadeghi Bahmani,1 Markus Gerber,2 Nadeem Kalak,1 Sakari Lemola,3 Peter J Clough,4 Pasquale Calabrese,5 Vahid Shaygannejad,6 Uwe Pühse,2 Edith Holsboer-Trachsler,1 Serge Brand1,2 1Psychiatric Clinics of the University of Basel, Center for Affective, Stress and Sleep Disorders, 2Department of Sport, Exercise and Health, Sport Science Section, University of Basel, Basel, Switzerland; 3Department of Psychology, University of Warwick, Coventry, 4Department of Psychology, Manchester Metropolitan University, Manchester, UK; 5Division of Molecular and Cognitive Neuroscience, University of Basel, Basel, Switzerland; 6Department of Neurology and Isfahan Neurosciences Research Center, Isfahan University of Medical Sciences, Isfahan, Iran Background: Multiple sclerosis (MS) is the most common chronic autoimmune demyelinating and inflammatory disease of the central nervous system, afflicting both the body and mind. The risk of suffering from MS is 2.5–3.5 times greater in females than in males. While there is extant research on fatigue, depression, and cognitive impairment in patients with MS during its clinical course, there is a lack of research focusing on sleep, psychological functioning, and physical activity (PA) at the point of disease onset. The aims of the present study were therefore, to assess the markers of mental toughness (MT) as a dimension of psychological functioning, sleep disturbances (SD), and PA among patients at the moment of disease onset and to compare these with the corresponding values for healthy adolescents and young adults. Methods: A total of 23 patients with MS at disease onset (mean age =32.31 years; 91% females), 23 healthy adolescents (mean age =17.43 years; 82% females), and 25 healthy young adults (mean age =20.72 years; 80% females) took part in the study. They completed questionnaires covering sociodemographic data, MT, SD, and PA. Results: Patients with MS had similar scores for MT traits as those in healthy adolescents and healthy young adults, and equivalent levels of moderate-intensity PA and SD as young adults. MS patients reported lower levels of vigorous PA compared to both healthy adolescents and young adults. Conclusion: The pattern of the results of the present study suggests that the onset of MS is not associated with poor MT, poor sleep, or reduced moderate-intensity PA. Lower levels of vigorous PA were observed in MS patients. Low levels of vigorous PA may lead to decreased cardiorespiratory fitness in patients with MS and, in the long run, to reduced cardiovascular health and degraded psychological functioning. Keywords: multiple sclerosis, illness onset, mental toughness, sleep disturbances, physical activity, healthy controls